Identification and characterization of candidate detoxification genes in Pharsalia antennata Gahan (Coleoptera: Cerambycidae) - Yang, An-Jin; Yin, Ning-Na; Chen, Dan-Lu; Guo, Yu-Ruo; Zhao, Yu-Jie; Liu, Nai-Yong (Frontiers in Physiology, 2022)
The wood-boring beetles, including the majority of Cerambycidae, have developed the ability to metabolize a variety of toxic compounds derived from host plants and the surrounding environment. However, detoxification mechanisms underlying the evolutionary adaptation of a cerambycid beetle Pharsalia antennata to hosts and habitats are largely unexplored. Here, we characterized three key gene families in relation to detoxification (cytochrome P450 monooxygenases: P450s, carboxylesterases: COEs and glutathione-S-transferases: GSTs), by combinations of transcriptomics, gene identification, phylogenetics and expression profiles. Illumina sequencing generated 668,701,566 filtered reads in 12 tissues of P. antennata, summing to 100.28 gigabases data. From the transcriptome, 215 genes encoding 106 P450s, 77 COEs and 32 GSTs were identified, of which 107 relatives were differentially expressed genes. Of the identified 215 genes, a number of relatives showed the orthology to those in Anoplophora glabripennis, revealing 1:1 relationships in 94 phylogenetic clades. In the trees, P. antennata detoxification genes mainly clustered into one or two subfamilies, including 64 P450s in the CYP3 clan, 33 COEs in clade A, and 20 GSTs in Delta and Epsilon subclasses. Combining transcriptomic data and PCR approaches, the numbers of detoxification genes expressed in abdomens, antennae and legs were 188, 148 and 141, respectively. Notably, some genes exhibited significantly sex-biased levels in antennae or legs of both sexes. The findings provide valuable reference resources for further exploring xenobiotics metabolism and odorant detection in P. antennata.